Meditation for subjective cognitive decline, mild cognitive impairment and Alzheimer’s disease: a systematic review and meta-analysis of randomized controlled trials - Shi, Jiaxin; Tian, Hao; Wei, Jingwen; Xu, Wenhan; Luo, Qin; Peng, Jin; Xia, Jun; Huai, Wenying; Xiong, Ying; Chen, Yunhui (Frontiers in Public Health, 2025)
BackgroundMeditation has gained increasing recognition as a simple, cost-effective, and non-invasive therapeutic approach for older adults with subjective cognitive decline (SCD), mild cognitive impairment (MCI), and Alzheimer’s disease (AD). This meta-analysis aimed to systematically evaluate its effectiveness on this population.MethodsA comprehensive search across nine databases was performed from inception to April 1, 2024, to identify eligible randomized controlled trials (RCTs). The primary outcome was global cognitive performance measured by the Mini-Mental State Examination (MMSE), while the secondary outcomes included sleep quality estimated through the Pittsburgh Sleep Quality Index (PSQI), health status assessed using the 36-Item Short Form Health Survey (SF-36), and depression evaluated with the Geriatric Depression Scale (GDS). This meta-analysis utilized R 4.3.1 software and adhered to the Cochrane Handbook and PRISMA reporting guidelines.ResultsA total of 25 RCTs published between 2013 and 2024 involving 2,095 participants were included in this study. The pooled findings demonstrated that meditation significantly improved global cognitive performance (MD 2.22, 95% CI: 0.83–3.62, p = 0.002), sleep quality (MD −1.40, 95% CI: −2.52 to −0.27, p = 0.015), and health status (MD 3.50, 95% CI, 0.45–6.56, p = 0.020). However, no significant effect was observed on depression compared to the control group (SMD −0.16, 95% CI: −0.63 to 0.31, p = 0.514).ConclusionThis meta-analysis suggests that meditation is an effective adjunct therapy for improving global cognitive performance, sleep quality, and health status in older adults with SCD, MCI, and AD. However, given the heterogeneity and limited sample sizes, these findings should be interpreted with caution. More large-scale and high-quality RCTs are needed to further substantiate these effects.